Visible-light-driven photocatalytic degradation of rhodamine B by Ag 2 CO 3 /Bi 2 WO 6 nanocomposites - Anukorn Phuruangrat (2019)
© 2019, Iranian Chemical Society. 0–10 wt% Ag 2 CO 3 /Bi 2 WO 6 nanosamples were prepared by hydrothermal method combined with solution precipitation–deposition method. The as-prepared samples were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy and UV–visible spectroscopy. They certified that spherical Ag 2 CO 3 nanoparticles supported on orthorhombic Bi 2 WO 6 nanoplates. Their photocatalytic activities were investigated through photodegradation of rhodamine B (RhB) under visible-light irradiation. In this research, 10 wt% Ag 2 CO 3 /Bi 2 WO 6 nanocomposites show the highest performance for photodegradation of RhB induced by visible radiation.